PERITONEAL ENCAPSULATION PRESENTING AS SMALL BOWEL OBSTRUCTION IN A 16 YEAR OLD GIRL - Shamsuddin, Syed; Bilal, Mohammad; Rehman, Bushra; Najeeb, Erum; Faisal, Sultan (Journal of Ayub Medical College Abbottabad, 2012)
Peritoneal encapsulation is a rare congenital anomaly characterized by a thin membrane of peritoneum encasing the small bowel to form an accessory peritoneal sac. Cases usually present with small bowel obstruction or can be an incidental finding during laparotomy. We report a case of peritoneal encapsulation presenting as a small bowel obstruction in a 16 year old girl. The sac was easily excised and surgery was otherwise uneventful. A discussion of the case and review of literature is presented.